2016
DOI: 10.1039/c6cp06135d
|View full text |Cite
|
Sign up to set email alerts
|

Toward a modular multi-material nanoparticle synthesis and assembly strategy via bionanocombinatorics: bifunctional peptides for linking Au and Ag nanomaterials

Abstract: Materials-binding peptides represent a unique avenue towards controlling the shape and size of nanoparticles (NPs) grown under aqueous conditions. Here, employing a bionanocombinatorics approach, two such materials-binding peptides were linked at either end of a photoswitchable spacer, forming a multi-domain materials-binding molecule to control the in situ synthesis and organization of Ag and Au NPs under ambient conditions. These multi-domain molecules retained the peptides' ability to nucleate, grow, and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…However, studies of Pt NP synthesis in aqueous media indicated that peptides could direct the production of shape-controlled NPs using seeded growth, , which suggests that a similar strategy could be successful for Au NPs. Moreover, a peptide-mediated strategy for shaped NP growth could also be used to direct the one-pot production and organization of NPs into assemblies . Our simulations also highlight the structural consequences of protonation state of the His residues, particularly at the Au(100)(1 × 1) facet.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…However, studies of Pt NP synthesis in aqueous media indicated that peptides could direct the production of shape-controlled NPs using seeded growth, , which suggests that a similar strategy could be successful for Au NPs. Moreover, a peptide-mediated strategy for shaped NP growth could also be used to direct the one-pot production and organization of NPs into assemblies . Our simulations also highlight the structural consequences of protonation state of the His residues, particularly at the Au(100)(1 × 1) facet.…”
Section: Resultsmentioning
confidence: 85%
“…Molecular simulation and computational chemistry can provide a crucial complementary perspective on this problem. ,,, Despite substantial progress in simulations of the peptide–Au interface, considerable challenges remain in terms of connecting the findings from molecular simulations to experimental data. To this end, three key conditions must be met for such molecular simulations to provide compelling insights: (1) a reliable description of the relevant interatomic interactions (particularly across the interface), (2) robust sampling of the conformational ensemble of the biomolecule, and (3) an appropriate structural model of the target substrate surface.…”
Section: Introductionmentioning
confidence: 99%
“…However, many of the more recent simulation studies of the peptide–materials biointerface involve the use of advanced conformational sampling. ,,,,, ,,,,, That said, we reiterate here that the use of advanced conformational sampling is a necessary, but not sufficient, factor in making physically reasonable predictions of abiotic/biotic interfacial interactions; the influences of the interfacial force field and the structural model of the substrate can also exert a critical influence on the simulation outcomes. For example, Sahai and co-workers reported the use of advanced conformational sampling (using parallel tempering metadynamics) to predict the adsorption free energies and structures of the aqueous peptide/hydroxyapatite (HAP) interface .…”
Section: Bioinspired Nanotechnologymentioning
confidence: 87%
“…While techniques such as UV–vis spectroscopy, transmission electron microscopy (TEM), selected area electron diffraction (SAED), and X-ray-based techniques have been exploited to study the inorganic core of these materials (refs , , , , , , , , , , , , and ), methods that specifically acquire data concerning the peptide structure at the biointerface are rather limited; however, a variety of techniques have been exploited to characterize this regime. Because of the complexity of the system to be characterized (multiple different lengths of peptides adsorbed onto a 2–10 nm particle dispersed in aqueous solution), analysis of the binding event of the peptides to two-dimensional surfaces has been explored, most notably via quartz crystal microbalance (QCM) analysis, ,,,,, surface plasmon resonance (SPR) spectroscopy, ,,,, and atomic force microscopy (AFM). , QCM specifically exploits the piezoelectric effect of quartz to measure the amount of matter adsorbed on the metal-coated sensor based on frequency changes . Using this information, binding thermodynamics can be extracted to quantify the affinity for the peptide to the target material surface, thus providing key information about the biointerfacial interactions.…”
Section: Bioinspired Nanotechnologymentioning
confidence: 99%
See 1 more Smart Citation